Semantic systems : the power of AI and knowledge graphs : 15th International Conference, SEMANTiCS 2019, Karlsruhe, Germany, September 9-12, 2019, Proceedings /: the power of AI and knowledge graphs : 15th International Conference, SEMANTiCS 2019, Karlsruhe, Germany, September 9-12, 2019, Proceedings. (2019) - Unknown
No abstract available